Full-length cDNA sequence analysis of 85 avian leukosis virus subgroup J strains isolated from chickens in China during the years 1988–2018: coexistence of 2 extremely different clusters that are highly dependent upon either the host genetic background or the geographic location - Peikun Wang; Min Li; Haijuan Li; Lulu Lin; Mengya Shi; Zhanming Gu; Yanli Gao; Teng Huang; Meilan Mo; Tianchao Wei; Ping Wei (Poultry Science, 2020)
During the process of transmission and spread of avian leukosis virus subgroup J (ALV-J) in chickens worldwide, the viral genome is constantly changing. A comprehensive and systematic study of the evolutionary process of ALV-J in China is needed. In this study, we amplified the full-length viral cDNA sequences of 16 ALV-J isolates of Yellow-chicken origin and analyzed and compared these sequences with another 69 ALV-J strains isolated during the years 1988–2018. These isolates were then sorted into 2 clusters: cluster I included isolates that mainly originated from the layers and White-feather broilers from northern China; cluster II included isolates mainly from the Yellow-chicken, most of them being from southern China. According to the sequence homologies of the whole genome and gag, pol, gp85, and gp37 genes, the ALV-J strains are more likely to randomly change in different directions from the original strain HPRS-103 as time passes. The results of entropy analysis of the sequences of gag, pol, and env revealed that the env gene had the largest variation, and the gag gene nonconserved sites are mainly concentrated in p19, p10, and p12. In addition, 84.71% (72/85) of the isolates had the 205-nucleotide (nt) deletion in the 3′UTR region, and 30.59% (26/85) of the isolates had the 125-nt to 127-nt deletion in the E element. Our study provides evidence for the coexistence of 2 extremely different clusters of ALV-J prevailing in China and in some other countries during the period of 1988–2018 and implies that the clusters are highly dependent on the host genetic background and the geographic location.